Early South Gaulish Samian ware from the southwestern settlement area of Brigantium/Bregenz (Austria) - Kopf, Julia (Rei Cretariae Romanae Fautorum Acta, 2017)
Since the middle of the 19th century a great amount of Terra Sigillata has been discovered in Bregenz, but only a fractional part of it has been scientifically processed and published so far. In fact only the so called “Bregenzer Kellerfund”, found in 1878, has been widely disseminated among Terra Sigillata experts, due to its scientific value as a closed find. The prominence of this deposit is the merit of Johann Jacobs, who published a preliminary report on the Kellerfund in 1912. Apart from this publication and mentions of Samian ware in excavation reports, R. Knorr was one of the first archaeologists to deal with this kind of pottery from Brigantium. In his work “Töpfer und Fabriken verzierter Terra Sigillata des ersten Jahrhunderts“, published in 1919, he illustrated some Tiberian respectively early Claudian relief-decorated vessels of the forms Drag. 29 and Drag. 11 from Bregenz, which were found together in 1913.